The evaluation model in a consensus Law - Casanova, Mª Antonia (Avances en Supervisión Educativa, 2015)
The text presents some of the current situations of the educational system, especially related to the assessment, which demonstrate the importance of properly designing this curricular element so that it contributes to the improvement of the quality of education, without limit or condition its internal processes.He is a proposal for incorporation into a new education law, consensual, in which determines that they should be evaluated both educational administration, educational institutions and learning of students, commenting on the contents in these three major fields and making some observations as to the approach to be followed.
Keywords: internal evaluation; external evaluation; evaluation of learning; educational quality